2018
DOI: 10.1111/apps.12163
|View full text |Cite
|
Sign up to set email alerts
|

Dark Motives and Elective Use of Brainteaser Interview Questions

Abstract: Brainteaser interview questions such as "Estimate how many windows are in New York" are just one example of aggressive interviewer behaviour that lacks evidence for validity and is unsettling to job applicants. This research attempts to shed light on the motives behind such behaviour by examining the relation between dark-side traits and the perceived appropriateness of brainteaser interview questions. A representative sample of working adults (n = 736) was presented with a list of interview questions that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…Although never published, internal research by Google concluded that brainteaser questions are "a waste of time" (Bryant, 2013). Indeed, conventional wisdom suggests that unconventional questions serve only to make interviewers feel smart (Highhouse et al, 2019) and have little value for selection or recruitment (Speer et al, 2020).…”
Section: Horse-sized Duck or Duck-sized Horses?mentioning
confidence: 99%
See 1 more Smart Citation
“…Although never published, internal research by Google concluded that brainteaser questions are "a waste of time" (Bryant, 2013). Indeed, conventional wisdom suggests that unconventional questions serve only to make interviewers feel smart (Highhouse et al, 2019) and have little value for selection or recruitment (Speer et al, 2020).…”
Section: Horse-sized Duck or Duck-sized Horses?mentioning
confidence: 99%
“…Unlike brainteaser questions, OPQs (1) do not require analytical problem solving, and (2) are related to aspects of an applicant's personality or biographical background. Existing research has either ignored this type of question altogether (Honer et al, 2007;Wright et al, 2012) or did not differentiate them from their cognitive-demanding counterparts (i.e., 'brainteasers'; Highhouse et al, 2019;Speer et al, 2019). Although there is considerable variability in how hiring professionals are using OPQs in a job interview context for decision making, recruitment research suggests that the use of OPQs could impact job seekers and applicants' experiences during the hiring process, which could have both immediate effects on applicant reactions (e.g., interview motivation) as well as downstream effects on recruitment outcomes (e.g., intentions to apply) (Breaugh, 2013).…”
Section: Horse-sized Duck or Duck-sized Horses?mentioning
confidence: 99%
“…For instance, Nolan, Carter, and Dalal (2016) found that managers feel that their sense of job-related competence is threatened if they use structured interviews. Instead, managers often prefer unstructured interviews (i.e., interviews without a specified set of questions) to exercise their autonomy, discretion, and power over the hiring process (Highhouse, Nye, & Zhang, 2018;Lievens & De Paepe, 2004). Many managers find the structured interview too rigid or simply not useful (Chen, Tsai, & Hu, 2008;Terpstra & Rozell, 1997).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…For instance, Nolan and colleagues (2016) found that managers feel that their sense of job-related competence is threatened if they use structured interviews. Instead, managers often prefer unstructured interviews (i.e., interviews without a specified set of questions) to exercise their autonomy, discretion, and power over the hiring process (Highhouse, Nye, & Zhang, 2018;Lievens & De Paepe, 2004). Many managers find the structured interview too rigid or simply not useful (Chen, Tsai, and Hu, 2008;Terpstra and Rozell, 1997).…”
Section: Communicating With Storytellingmentioning
confidence: 99%